Correlation of xerostomia in methadone therapy program patient with oral health related quality of life using oral health impact profile-14: a cross-sectional study - Theresia, Tiarma Talenta; Fitri, Andrian Nova; Sudhana, Widijanto; Astoeti, Tri Erri (Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: Methadone Therapy Program (MTP) patients receive treatment with antidepressants which work as salivary flow inhibitors that promote xerostomia. Decreased salivary secretion affects several essential aspects of life quality, such as speaking, chewing, and food swallowing. It also increases the risk of rampant caries. This study aimed to analyze correlation of xerostomia in MTP with Oral Health Related Quality of Life (OHRQoL) using the Oral Health Impact Profile (OHI-P 14). Methods: Type of research was a cross-sectional design, this study's main independent variable was xerostomia, the dependent variable was OHRQoL, and the confounders were age, gender, education, occupation, caries status, oral hygiene status, history of HIV infection, smoking habits, and alcohol consumption. Data analysis used logistic regression to see the risk factors that influence OHRQoL. Results: Xerostomia is a subjective dry mouth complaint asked through a questionnaire. Of the 26 respondents, 13 (50%) reported dry mouth. Salivary Flow Rate (SFR) measurement showed the result of 13 people was <0.3 (hyposalivation). OHrQOL was measured using OHI-P 14 questionnaire, 12 respondents had good OHRQoL (score > 6.5) and 13 respondents had bad (score ≤6.5). Risk factors associated with OHRQoL were age (p=0.08) and duration of methadone consumption (p=0.06). Conclusion: There is no correlation between xerostomia in MTP with Oral Health Related Quality of Life (OHRQoL) using the Oral Health Impact Profile (OHI-P 14). Future research should involve several hospitals that carry out MTP so that the research results are more valid.KEYWORDSmethadone, oral health related quality of life, OHrQOL, OHIP-14, xerostomia